A comprehensive assessment of the transcriptome of cork oak (Quercus suber) through EST sequencing. - Pereira-Leal, José B; Abreu, Isabel a; Alabaça, Cláudia S; Almeida, Maria Helena; Almeida, Paulo; Almeida, Tânia; Amorim, Maria Isabel; Araújo, Susana; Azevedo, Herlânder; Badia, Aleix; Batista, Dora; Bohn, Andreas; et al. (BMC genomics, 2014)
BACKGROUND: Cork oak (Quercus suber) is one of the rare trees with the ability to produce cork, a material widely used to make wine bottle stoppers, flooring and insulation materials, among many other uses. The molecular mechanisms of cork formation are still poorly understood, in great part due to the difficulty in studying a species with a long life-cycle and for which there is scarce molecular/genomic information. Cork oak forests are of great ecological importance and represent a major economic and social resource in Southern Europe and Northern Africa. However, global warming is threatening the cork oak forests by imposing thermal, hydric and many types of novel biotic stresses. Despite the economic and social value of the Q. suber species, few genomic resources have been developed, useful for biotechnological applications and improved forest management. RESULTS: We generated in excess of 7 million sequence reads, by pyrosequencing 21 normalized cDNA libraries derived from multiple Q. suber tissues and organs, developmental stages and physiological conditions. We deployed a stringent sequence processing and assembly pipeline that resulted in the identification of ~159,000 unigenes. These were annotated according to their similarity to known plant genes, to known Interpro domains, GO classes and E.C. numbers. The phylogenetic extent of this ESTs set was investigated, and we found that cork oak revealed a significant new gene space that is not covered by other model species or EST sequencing projects. The raw data, as well as the full annotated assembly, are now available to the community in a dedicated web portal at http://www.corkoakdb.org. CONCLUSIONS: This genomic resource represents the first trancriptome study in a cork producing species. It can be explored to develop new tools and approaches to understand stress responses and developmental processes in forest trees, as well as the molecular cascades underlying cork differentiation and disease response.
APS
Keywords: Cork oak; EST sequencing; Quercus suber; transcriptome

Expression of DNA methyltransferases is involved in Quercus suber cork quality - Ramos, Miguel; Rocheta, Margarida; Carvalho, Luísa; Inácio, Vera; Graça, José; Morais-Cecílio, Leonor (Tree Genetics & Genomes, 2013)
Abstract Cork oak (Quercus suber ) is an important Portuguese species, mainly due to the economic value of the cork it produces. Cork results from phellogen, a meristematic tissue, which can locally produce lenticels or have discontinu- ities, originating “defects”: pores and nail inclusions that are detrimental to cork industrial use. Epigenetic processes control plant development and its deregulation can lead to altered phenotypes; therefore, the study of epigenetic players in the phellogen is important to understand the emergence of cork's defects. DNA methyltransferases (DNMTs) and one protein associated to MET1 (DMAP1) were characterized in Q. suber, and their gene expression was analyzed in phellogen and con- tiguous differentiating cell layers of trees producing high and low quality cork, after the evaluation of their defects by physical and image analysis methods. All classes of DNMTs (MET, DRM, and CMT) with the respective canonical motifs were identified in Q. suber. The expression analyses of these genes showed that QsDRM2 was the most active methyltransferases in the cells analyzed, and that all the genes were differentially expressed in trees with distinct cork quality,with a tendency for higher expression levels in lowquality producers. Interestingly, the global methylation level was higher in cells with low expression of DNA methyltransferases. A positive and significant correlation was obtained between QsDMAP1 gene expression and the percentage of cork defects. This work provides the first evidence that cork quality in Q. suber is likely influenced by epigenetic mechanisms
Keywords: CMT3; Cork oak; Cork quality; DMAP1; DRM; MET1; MET2; phellogen activity